(untitled) (Alberta Journal of Educational Research, 2020)
This mixed methods case study investigated faculty perspectives and practice around plagiarism in a Western Canadian faculty of education. Data sources included interviews, focus groups, and a survey. Findings showed that participants (N = 36) were disinclined to follow established procedures. Instead, they tended to deal with plagiarism in informal ways without reporting cases to administration, which resulted in a disconnect between policy and practice. The emotional impact of reporting plagiarism included frustration with the time required to document a case, and fear that reporting could have a negative effect on one’s employment. Recommendations include approaches that bridge the gap between policy and practice. Key words: Academic integrity, plagiarism, Canada, higher education, faculty Cette étude de cas à méthodes mixtes s’est penchée sur les perspectives et les pratiques du corps professoral relatives au plagiat dans une faculté d’éducation dans l’ouest du Canada. Les sources de données ont inclus les entrevues, les groupes de discussion et un sondage. Les résultats indiquent que les participants (N=36) étaient peu portés à suivre les procédures établies. Ils avaient plutôt tendance à employer des moyens informels pour traiter le plagiat, sans signaler les cas à l’administration, ce qui entrainait un écart entre la politique et la pratique. L’impact émotionnel découlant du signalement du plagiat comprenait le temps nécessaire à documenter un cas et la peur que le signalement puisse avoir une incidence négative sur son emploi. Les recommandations proposées incluent des approches visant à combler l’écart entre la politique et la pratique. Mots clés : intégrité académique, plagiat, Canada, enseignement supérieur, faculté